Perkembangan Keamanan Siber Indonesia melalui ASEAN Regional Forum (ARF) - Vivekananda, Visvanathan Gabriel Matrix Baruna; Widya Nugraha, A.A. Bagus Surya; Putri, Penny Kurnia (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2025)
The rapid expansion of the digital world has ushered in a new era of global connectedness, offering limitless opportunities while presenting significant security challenges. This research investigates Indonesia's journey in improving its cybersecurity posture through the ASEAN Regional Forum (ARF). In a world where cyber threats transcend national boundaries and impact both state and non-state actors, Indonesia recognises the importance of maintaining its national security in cyberspace based on the White Defence Paper, which acknowledges that cyberspace is becoming the fifth domain of war. Based on secondary data, it is analysed that the momentum of Indonesia's leadership in the ARF has the potential to increase the country's cybersecurity development. This is based on various agendas and partnerships within the ARF, which have direct and indirect impacts on Indonesia's cybersecurity development. The development of cybersecurity generated through the ARF on Indonesia's national security in cybersecurity has an impact on two categories of cyber threats based on Choucri. This is shown in 1) Cyber threats to infrastructure obtained from the Cyber and Critical Tech Cooperation Programme & ASEAN Cyber Capacity Development Project and 2) Cyber terrorism obtained from the ASEAN Cyber Capability and Capacity Development Project programme. Indonesia has been able to utilise the ARF platform to enhance the development of the country's cybersecurity during its leadership in the ARF.